Examining the impact of abusive supervision on employees' psychological wellbeing and turnover intention: The mediating role of intrinsic motivation - Kanwal Hussain; Zuhair Abbas; Saba Gulzar; Abdul Bashiru Jibril; Altaf Hussain (Cogent Business & Management, 2020)
The competitiveness and sustainability of employees in service and non-service-based organizations continue to trigger scholars' interest to investigate the related factors. As per the review of literature, there are only a few studies have been conducted on abusive supervision and intrinsic motivation about employee psychological wellbeing and turnover intention. We applied the social exchange theory to abusive supervisors at the workplace. This study, therefore, explores the direct and indirect relationship between abusive supervision on subordinate psychological wellbeing and turnover in service-based organizations. This empirical study employs a quantitative research methodology to establish the mediating influence of intrinsic motivation between the underlying constructs. Out of 300 research questionnaires distributed to full-time employees working in service-based organizations in Pakistan, 225 responses were successful for analysis, and validation was conducted through partial least square structural equation modelling (PLS-SEM). The results of this study demonstrate that abusive supervision (AS) positively impacting on both psychological wellbeing (PWB) and turnover intentions (TI) of the employees. More importantly, intrinsic motivation (IM) is also positively and significantly mediate the relationship between AS and PWB, and AS and TI. The study provides substantial implications to managers and leaders by redesigning existing strategies to promote a feasible culture within the working environment for the employees to improve performance. The current study enhances existing literature on employee wellbeing and human resource management by integrating intrinsic motivation (IM) as a mediation model/concept. Limitations and future research directions have been discussed in the entire paper.
Keywords: M1; M12; M14; 650; abusive supervision; psychological wellbeing; intrinsic motivation; turnover intention; Pakistan